2020
DOI: 10.3390/agronomy10091411
|View full text |Cite
|
Sign up to set email alerts
|

1-Methylcyclopropene on Fruit Quality of Se-Enriched Grape (Vitis vinifera L.) during Shelf Life Period

Abstract: Selenium (Se) deficiency in humans could be improved by biofortification of food with selenium, 1-Methylcyclopropene (1-MCP) treatment is beneficial for the non-sulfur storage of fresh fruit. This study investigated fruit quality of table grape (Hutai No.8) with foliar Se fertilizer at maturity, and fruit quality changes of table grape during shelf life stages that caused by postharvest 1-MCP treatment in 2016 and 2017. The results showed that foliar Se fertilizer application significantly increased Se content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The 1-MCP could be applied both pre [16,17] and postharvest [18,19] as a treatment being non-toxic, stable over time and improving the quality of the products. In spite of the fact that it is applied mainly for apples, it may be used also for other fruit and vegetables, but the role of ethylene in ripening and senescence processes may differ, depending on the product, so also responses to 1-MCP are various [20].…”
Section: Introductionmentioning
confidence: 99%
“…The 1-MCP could be applied both pre [16,17] and postharvest [18,19] as a treatment being non-toxic, stable over time and improving the quality of the products. In spite of the fact that it is applied mainly for apples, it may be used also for other fruit and vegetables, but the role of ethylene in ripening and senescence processes may differ, depending on the product, so also responses to 1-MCP are various [20].…”
Section: Introductionmentioning
confidence: 99%
“…The CEL content of immature fruits is low, and CEL activity in immature fruits increases significantly in the later stages of fruit ripening and softening. It has previously been shown that 1‐MCP treatment can significantly inhibit CEL activity in Niagara grapes (Liu et al ., 2022b), Kyoho grapes (Leng et al ., 2022), and the Cabernet Sauvignon winegrape (Zhu et al ., 2020). We found that S‐MAP generated by LMF effectively suppressed respiration and enhanced the inhibition of CEL activity when it was combined with the 1‐MCP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 1-MCP is widely used in blueberries [8], sweet cherries [9], and other fruits to preserve their excellent quality. Furthermore, 1-MCP has been shown to effectively maintain the storage quality of "Crystal" grapes and other table grapes [10,11]. Zhu et al [11] found that fumigating selenium-rich grapes with 1.0 µL/L 1-MCP can effectively maintain the selenium content, and improve the sugar, titratable acidity (TA), and amino acids content during storage, thus enhancing the edible value of the fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 1-MCP has been shown to effectively maintain the storage quality of "Crystal" grapes and other table grapes [10,11]. Zhu et al [11] found that fumigating selenium-rich grapes with 1.0 µL/L 1-MCP can effectively maintain the selenium content, and improve the sugar, titratable acidity (TA), and amino acids content during storage, thus enhancing the edible value of the fruits. Moreover, the inhibition of various substances associated with fruit ripening, such as lycopene, chlorophyll, peel color, and polygalacturonic (PG) activity, has also been observed [12].…”
Section: Introductionmentioning
confidence: 99%